Phytoextraction of heavy metals from a multiply contaminated dredged sediment by chicory (Cichorium intybus L.) and castor bean (Ricinus communis L.) enhanced with EDTA, NTA, and citric acid application. Issue 13 (10th November 2018) - Bursztyn Fuentes, A. L.; José, C.; de los Ríos, A.; do Carmo, L. I.; de Iorio, A. F.; Rendina, A. E.
Abstract: The remediation of contaminated dredged sediments is necessary to eliminate the risk towards human beings or the environment when there is disposal on land. A greenhouse experiment was carried out to evaluate the chemically assisted phytoextraction to clean up dredged sediment contaminated with Cr, Cu, Pb, and Zn. The ability of castor bean and chicory to absorb, translocate, and accumulate metals from sediment to root and shoot was evaluated by applying EDTA (5 mM), NTA (5 mM), and citric acid (60 mM) to sediment, before the harvest. Citric acid 60 mM was the most effective treatment in increasing Cr, Cu, and Pb in castor bean and chicory shoot. Chicory could accumulate 1730 mg Cr kg −1 in shoot, and had greater values than one for the bioaccumulation and translocation factors when citric acid was added to the sediment. But, the Cr percentages removed per harvest of chicory were 0.05% and were lower for Cu, Pb, and Zn due to low biomass obtained. Citric acid-assisted phytoextraction with chicory can be a promising short time solution to reduce Cr concentration in sediment and reach the Cr level guide for industrial land use only if suitable agronomic practices could be implemented to increase crop yield.